2018
DOI: 10.1038/s41598-018-19530-8
|View full text |Cite
|
Sign up to set email alerts
|

APLP1 is endoproteolytically cleaved by γ-secretase without previous ectodomain shedding

Abstract: Regulated intramembrane proteolysis of the amyloid precursor protein (APP) and its homologs, the APP like proteins APLP1 and APLP2, is typically a two-step process, which is initiated by ectodomain-shedding of the substrates by α- or β-secretases. Growing evidence, however, indicates that the cleavage process for APLP1 is different than for APP. Here, we describe that full-length APLP1, but not APP or APLP2, is uniquely cleaved by γ-secretase without previous ectodomain shedding. The new fragment, termed sAPLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…Laurent et al (2015), Schauenburg et al (2018) Family members with known shedding function are indicated in bold and italics. Selected review articles are given that typically describe the whole protease family.…”
Section: Plasma Membrane Endosomesmentioning
confidence: 99%
“…Laurent et al (2015), Schauenburg et al (2018) Family members with known shedding function are indicated in bold and italics. Selected review articles are given that typically describe the whole protease family.…”
Section: Plasma Membrane Endosomesmentioning
confidence: 99%
“…The Amyloid-like protein 1 (APLP1), a member of the APP family, was found to consistently decrease in 3 independent studies. This neuron-specific protein [69] is involved in the maintenance of dendritic spines and basal synaptic transmission [70]. APLP1 is a γ-secretase substrate [71], thereby, secreted APLP1 fragments might be of especial interest to investigate γ-secretase cleavage products in AD.…”
Section: Proteins Consistently Reduced In Ad Csfmentioning
confidence: 99%
“…Of course, of the three APP-related proteins, only APP itself can produce the Aβ peptide. Despite its close similarity to APP, the protein APLP1 apparently does not require cleavage by α- or β-secretase in order to be cleaved by γ-secretase ( Schauenburg et al, 2018 ). However, both APLP1 ( Li and Sudhof, 2004 ) and APLP2 ( Pastorino et al, 2004 ) can be cleaved by β-secretase ( Pastorino et al, 2004 ), and Aβ-equivalent peptides have been detected for these proteins ( Eggert et al, 2004 ; Yanagida et al, 2009 ) although there is little to suggest that these peptides have pathological activity.…”
Section: An Alternative Link Between Eofad-associated Mutations In Apmentioning
confidence: 99%